2020
DOI: 10.1101/2020.06.08.20125682
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A community-based validation of the International Alliance for the Control of Scabies Consensus Criteria by expert and non-expert examiners in Liberia

Abstract: Background The International Alliance for the Control of Scabies (IACS) recently published expert consensus criteria for scabies diagnosis. Formal validation of these criteria is needed to guide implementation. We conducted a study to provide detailed description of the morphology and distribution of scabies lesions as assessed by dermatologists and validate the IACS criteria for diagnosis by both expert and non-expert examiners. Methods Participants from a community in Monrovia, Liberia, were independently a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
2
5
1
Order By: Relevance
“…For example, our results show that the dorsal aspect of the finger web spaces is much more commonly involved than the palmar web spaces. One previous study showed an increased frequency of involvement of the dorsal hand compared to the palmar hand 18 . Similarly, where previous studies have reported the arms to be common sites for lesions, 14,23,31 our study and choropleth figures reveal this in greater detail, including the preponderance for lesions on the medial and anterior arm 14,25,32 …”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…For example, our results show that the dorsal aspect of the finger web spaces is much more commonly involved than the palmar web spaces. One previous study showed an increased frequency of involvement of the dorsal hand compared to the palmar hand 18 . Similarly, where previous studies have reported the arms to be common sites for lesions, 14,23,31 our study and choropleth figures reveal this in greater detail, including the preponderance for lesions on the medial and anterior arm 14,25,32 …”
Section: Discussionsupporting
confidence: 84%
“…An even more limited examination such as only the hands and wrists (sensitivity 93%) or only the arms (sensitivity 97%) could also be considered. These sensitivities are slightly higher than previous estimates of limited examinations which ranged from 92% to 93% 17,18 . Focused examination may miss a small number of cases in infants and young children (sensitivity 88% for hands and wrists, 96% for arms).…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations